Settling in Norway? The Case of Polish Migrants and Their Families (Economic and Political Thought, 2016)
People of Polish origin constitute not only the largest group of immigrantsin Norway (99,424 in 2015, Statistics Norway), but also the largest group ofimmigrants in many Norwegian municipalities. This article presents differentpatterns of settlement choices and spatial experiences of Polish migrants andtheir families in Norway. Based on the analysed material, it can be concludedthat we are witnessing a process of settlement of Polish migrants in Norway.Regardless of their initial plans, currently they see their future in Norway,not in Poland. Their activities in Norway are not limited to work exclusively,they start families there or bring family members who used to live in Poland,they buy flats and houses, send their children to Norwegian kindergartensand schools.